Pengembangan Media Powtoon Bernilai Karakter Ilmu Pengetahuan Sosial di Sekolah Dasar - Ninik Indawati; Azizatur Rosyidah; Cicilia Ika Rahayu Nita; Delita Pristyowati (Universitas Negeri Padang, 2022)
The purpose of this study was to develop Powtoon media with the value of social studies characters on Javanese traditional houses for fifth grade elementary school students. The research method that has been used is Research & Development referring to the Borg & Gall model with the stages of problem analysis, design design, design implementation, testing, expert validation, media improvement, feasibility test, media improvement, and implementation. The subjects of this study were students at the fifth level of Kebonsari 4 State Elementary School, Malang City. Data analysis techniques through qualitative and quantitative descriptive. The result is a material validation score of 95.8%., a language validation score of 87.5%., a media validation score of 92.9%. The results of the validation of the effectiveness obtained a score of 91.9%. Thus, Powtoon media is of high quality and suitable for use in learning activities.